Understanding the Students’ Adversities in the Science Classroom - Solis-Foronda, Marisol; Marasigan, Arlyne C. (Journal of Education and e-Learning Research, 2021)
Science has long been regarded as an important subject in a school curriculum and science teachers play a vital role in the learning process of the students in the science classrooms as well as in other subjects. However, students still encounter problems related to their science teachers, which significantly influence their academic performance in science. Using a qualitative-phenomenological design, an in-depth and systematic analysis of the students’ experiences gathered during the face-to-face interview provided a detailed explanation of the teacher-based adversities in the science classroom. The students who participated in this study revealed that they had encountered various teacher-based adversities, which disrupted and affected their learning and performance in the science classroom. Students experienced having a teacher of limited pedagogical content knowledge in science, and little commitment to teach science in the classroom. Consequently, the students were not encouraged to learn science; they lost interest to learn science as well as they have developed a negative attitude towards their teachers and the subject. In the same manner, the students experienced difficulty in understanding the topic and inability to connect previous information to a new one because of having a teacher of little commitment in the instruction of science. With this, the interested parties such as the teachers, administrators, students can develop appropriate actions to address these problems not only in the science classroom but in the school in general.